Mosque Design at Living Lab with Local Wisdom Approach - Dara Wisdianti; Novalinda Novalinda; Peranita Sagala; Fadillah Fadillah (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
The Al-amin Science And Industrial Park area is projected to become a center for field laboratories and workshops that accommodate all study programs at UNPAB. In addition, the Al-amin Science And Industrial Park area is also planned to be the location of Ecoedutourism (Ecoedutourism) based on agriculture and processing of agricultural products. Eco-education is expected to attract visitors to enjoy the location of the Al-amin Science And Industrial Park Area with attractions based on field activities from study programs at UNPAB such as horticultural gardens, nurseries, animal husbandry, waste management for the use of renewable energy to processing packaging of garden and livestock products. The construction of the Al-amin Science And Industrial Park Area Mosque is expected to become a center of Islamic activities consisting of worship activities, mu'amalah and da'wah education, as well as Islamic information centers, not only for the Al-amin Science And Industrial Park area but also for the surrounding community and visitors to the area.